2014
DOI: 10.2217/nmt.14.21
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oligodendroglial Dysfunction in Amyotrophic Lateral Sclerosis

Abstract: Healthy oligodendrocytes are crucial for neurons and abnormal functioning of these cells is involved in several neurodegenerative diseases. We will focus on oligodendroglial pathology in amyotrophic lateral sclerosis (ALS), an adult-onset progressive neurodegenerative disease characterized by selective motor neuron loss. Recent discoveries shed new light on the crucial role of oligodendrocytes in this fatal disease. We will first give an overview of the importance of good-functioning oligodendrocytes for neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 144 publications
(221 reference statements)
2
39
1
Order By: Relevance
“…One of the major discoveries involving G93A‐SOD1 mice is that ALS is not cell specific, which means that glial cells surrounding motor neurons are probably involved in the mechanisms leading to the selective death of motor neurons, and specific differences have been described between axonal damage and reduction in myelin content using DTI . In particular, our study aimed to unveil the role of RD and myelin degeneration in ALS at earlier stages of the disease . Consistent with previous reports of oligodendrocyte impairments in ALS, our investigations determined a presymptomatic increase in RD associated with an early reduction in MBP in YFP,G93A‐SOD1 mice (Figure a, b).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…One of the major discoveries involving G93A‐SOD1 mice is that ALS is not cell specific, which means that glial cells surrounding motor neurons are probably involved in the mechanisms leading to the selective death of motor neurons, and specific differences have been described between axonal damage and reduction in myelin content using DTI . In particular, our study aimed to unveil the role of RD and myelin degeneration in ALS at earlier stages of the disease . Consistent with previous reports of oligodendrocyte impairments in ALS, our investigations determined a presymptomatic increase in RD associated with an early reduction in MBP in YFP,G93A‐SOD1 mice (Figure a, b).…”
Section: Discussionsupporting
confidence: 84%
“…41,71,72 In particular, our study aimed to unveil the role of RD and myelin degeneration in ALS at earlier stages of the disease. 70,73 Consistent with previous reports of oligodendrocyte impairments in ALS, 73,74 our investigations determined a presymptomatic increase in RD associated with an early reduction in MBP in YFP,G93A-SOD1 mice (Figure 4a, b). Remarkably, patterns of alterations in RD followed a similar arrangement to alterations previously described in axonal microstructure and organization (measured by FA).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we have shown that S100B is expressed at low levels in healthy animals, as it was expected. Its localization is mostly restricted to the white matter, where it also appears in CNPase-positive mature oligodendrocytes, which staining instead decreases in affected tissues probably due to oligodendrocyte degeneration, a recently described phenomenon occurring in both patients and rodent models of the disease [35]. Overall, S100B staining increases in SOD1 G93A tissues, and, in particular, it is massively expressed by GFAP-positive astrocytes with typical reactive phenotypes.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies show that corticospinal motor neurons mirror some of the earliest signs of degeneration that occur in lower motor neurons41, including early electrophysiological changes, dendritic regression and cell loss424344. Additionally, dysfunctional astrocytes, microglia and oligodendrocytes have been shown to contribute to disease progression and motor neuron degeneration in SOD1 mice454647484950, increasing interest in the role of cortical neuronal and non-neuronal populations in these models4651. Indeed, with the recent detection of early hyperexcitability in the motor cortex of patients, these and other studies support a cortical origin of disease469, initiated by cortical dysfunction, subsequently spreading to spinal motor neurons652.…”
Section: Discussionmentioning
confidence: 99%